Newborn with Gastroschisis associated with Limb Anomalies - Phyu Phyu Win (EL-Med-Pub, 2016)
Gastroschisis is often found together with other extra intestinal conditions such as limb, spine, cardiac, central nervous system and genitourinary abnormalities. There are reports of its association with young maternal age. The cases presented here highlight the association of gastroschisis with limbs anomalies and young maternal age.